THE DEVELOPMENT OF ELECTRONIC GUIDEBOOK FOR THE IMPLEMENTATION OF PROCUREMENT - Nikijuluw, Vanessa Christina Paskah; Faslah, Roni; Rachmadania, Rizki Firdausi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to produce an e-book guide on the implementation of procurement of goods and services, which helps employees and partner companies understand general provisions such as policies, rights and obligations, sanctions, and the procurement process of goods and services at PT. Pelabuhan Indonesia (Persero). The study uses the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Based on expert trials, the e-book received an average validity value of 81%, which means